2004
DOI: 10.1021/je049929f
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Volumetric Properties of Three Monoethylene Glycol Alkyl Ethers

Abstract: In the present work, the effect of pressure and temperature on the density, isobaric thermal expansivity, αp, isothermal compressibility, κT, and internal pressure, π of monoethylene glycol methyl ether (MEGME), monoethylene glycol ethyl ether (MEGEE), and monoethylene glycol isopropyl ether (iso-MEGPE) has been determined. New density data (273 experimental points) have been obtained with a vibrating tube densimeter at temperatures between (293.15 and 353.15) K and pressures up to 60 MPa. The trend of the vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The standard deviations are lower than the experimental uncertainty for the six oils. The three equations correlate the experimental data excellently, with average absolute deviations, AADs, lower or equal to 0.03%. The lowest-quality fit corresponds to motor oil with the Tammann-Tait equation for which the maximum deviation (0.14%) was found.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The standard deviations are lower than the experimental uncertainty for the six oils. The three equations correlate the experimental data excellently, with average absolute deviations, AADs, lower or equal to 0.03%. The lowest-quality fit corresponds to motor oil with the Tammann-Tait equation for which the maximum deviation (0.14%) was found.…”
Section: Resultsmentioning
confidence: 64%
“…The behavior of the viscosity at 0.1 MPa as a function of temperature, η­( T ), was described using the following modification of Andrade’s equation also known as three-coefficient Vogel–Fulcher–Tammann (VFT) equation: The values obtained for A , B , and C are gathered in Table S3. The average absolute deviations, AAD, of these correlations are lower than 1.3% for all the base oils. The glass-transition temperature is often defined as that at which the shear viscosity of the liquid is 10 12 Pa s .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Several authors have reported density data for wide ranges of pressures and temperatures for glymes. Comuñas and co-workers presented density data for EGEE, DEGDME, TriEGDME, and TeEGDME within the 293–353 K and 0.1–60 MPa temperature and pressure ranges, respectively. The experimental data reported here shows percentage absolute average deviations (%AARDs) of 0.75%, 0.04%, 0.05%, and 0.03%, respectively, against their data, as depicted in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In this work, we developed a new parameter set for each of the four solvents. The new sets were determined by fitting to the recommended vapor pressure data developed in this work (from Table ) and experimental liquid density data from the literature (ref for dimethoxymethane, refs and for 1,2-dimethoxyethane, ref for 2-methoxyethanol, and ref for 2-ethoxyethanol) using the simulated annealing optimization technique . The obtained parameters are shown in Table together with average absolute relative deviation (AARD) values between calculated and experimental data.…”
Section: Resultsmentioning
confidence: 99%